Preferences for Shigellosis-Related Health Promotion Materials for Gay, Bisexual, and Other Men Who Have Sex With Men: Results From a Qualitative Assessment, Atlanta, GA. Issue 4 (8th April 2022) - Respress, Ebony; Evener, Steve L.; Caruso, Elise; Jacobson, Kathleen; Bowen, Anna; Kachur, Rachel E.; Garcia-Williams, Amanda G.; Wright, Eric R.
Abstract : A qualitative examination of preferences for shigellosis health communication materials among men who have sex with men in Atlanta, GA found that gay and bisexual men prefer materials that are informative, provocative, but nonstigmatizing. Supplemental digital content is available in the text. Abstract : Background: Shigellosis, an acute diarrheal disease, is the third most common bacterial infection in the United States. Shigellosis most commonly affects children younger than 5 years; however, clusters and outbreaks of shigellosis have been reported among gay, bisexual, and other men who have sex with men (MSM). Evidence suggests that knowledge of shigellosis among MSM is low, indicating health promotion outreach is needed for this population. Methods: To inform the development of shigellosis-related health communication materials and strategies, 6 focus groups were conducted in 2017, in Atlanta, GA among 24 self-identified gay and bisexual men. Participants were asked about their preferences and recommendations for health communication materials. Results: Participants indicated they would prefer a range of physical and virtual materials placed in diverse locations where the community would see them. Respondents recommended health messages be simple, quick to read, and concise with limited word counts. Participants also advised the use of diverse images that were inclusive of couples of varying sexual orientations to reduce stigma. Participants advocated for the use of humor and provocative images to increase user engagement. Conclusions: The results emphasize the potential benefits of conducting formative research when designing health communication materials. Incorporating messaging preferences of MSM in the development of shigellosis-related health communication materials could enhance their relevance for the target population while also avoiding unintended consequences associated with stigmatizing MSM.